Graphitic carbon nitride nanoribbon for enhanced visible-light photocatalytic H2 production. Issue 113 (28th November 2016) - Bu, Xiuming; Bu, Yu; Yang, Siwei; Sun, Feng; Tian, Linfan; Peng, Zheng; He, Peng; Sun, Jing; Huang, Tao; Wang, Xianying; Ding, Guqiao; Yang, Junhe; et al.
Abstract : Chemical scissors provide a new vision to manufacture unique carbon nitride nanostructures with improved photocatalytic performance. Abstract : Chemical scissors provide a new vision to manufacture unique carbon nitride nanostructures with improved photocatalytic performance. Herein, graphitic carbon nitride nanoribbon (GCNR), with a typical length of 1.75 μm, width of 210 nm and thickness of 3 nm, was obtained by acid treatment of bulk g-C3 N4 with HNO3 /H2 SO4 mixtures. The C/N molar ratio of GCNR (around 0.629) was much smaller than that of pristine g-C3 N4 (0.758). It was demonstrated that larger amounts of carbon vacancies on the ultra-thin ribbon structures could contribute to improved electron–hole separation efficiency and excellent photocatalytic H2 production. The average H2 production rate of GCNR under visible light was 49.4 μmol h −1, which was 20 times that of the original catalyst.